ASSESSING WIND DIRECTION DIVERGENCE IN RELATION TO URBAN AREAS: A GIS METHODOLOGICAL FRAMEWORK - Cremon, Édipo Henrique; Alves , Gláucia de Sousa; Pereira, Gabriel (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
This study presents a methodology within a Geographic Information System (GIS) environment to evaluate the divergence of wind direction in relation to urban areas, with the objective of supporting the location of odor-generating facilities. The approach was organized into three main stages: obtaining the prevailing wind direction from interpolated raster data; calculating the orientation of each pixel relative to the nearest urban area; and comparing these directions through a function that computes the smallest angular difference adjusted within the range of 0° to 180°. The analysis produced a raster dataset that allows the identification of areas of greater convergence, where potential impacts on urban zones are more significant, and areas of greater divergence, more suitable for the location of facilities. The color-scale representation facilitated visual interpretation, distinguishing unfavorable and favorable regions for the location of odor-generating facilities. The approach demonstrates practical applicability for guiding the location of wastewater treatment plants, landfills, and industries, contributing to the mitigation of environmental and social impacts and providing support for sustainable urban planning policies.